2020
DOI: 10.1038/s41598-020-69902-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel predictive score for citrate accumulation among patients receiving artificial liver support system therapy with regional citrate anticoagulation

Abstract: Patients with liver failure may suffer citrate accumulation when using regional citrate anticoagulation for artificial liver support system therapy (RCA-ALSS therapy). This study aimed to develop a predictive scoring system to stratify the risk of citrate accumulation. A total of 338 patients treated with RCA-ALSS therapy were retrospectively enrolled and randomly divided into derivation and validation cohorts. Longer duration of citrate accumulation (LDCA) was defined as the presence of citrate accumulation 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Boer et al [15] performed a multivariate analysis using mixed-effects models for elevation of total/ionized calcium in patients with nonhepatic dysfunction who underwent CRRT. Another recent study about the risk assessment of CA in patients receiving artificial liver support system therapy also developed a multivariable prediction model [16]. We referenced the methodologies of these articles and used generalized linear mixed-effect models to analyze our data to develop a predictive model for the risk of CA in liver transplant patients undergoing CRRT with RCA.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boer et al [15] performed a multivariate analysis using mixed-effects models for elevation of total/ionized calcium in patients with nonhepatic dysfunction who underwent CRRT. Another recent study about the risk assessment of CA in patients receiving artificial liver support system therapy also developed a multivariable prediction model [16]. We referenced the methodologies of these articles and used generalized linear mixed-effect models to analyze our data to develop a predictive model for the risk of CA in liver transplant patients undergoing CRRT with RCA.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Other studies [8, 14] also confirmed that lactate was critical for the prediction of CA. Many studies have evaluated a single predictor for CA; however, studies of multivariate analyses for CA have been published recently [15, 16]. We believe that CA is multifactorial, and before administering RCA to liver transplant patients with liver dysfunction, a clinician should consider the risk of CA to make appropriate anticoagulation decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Regional citrate anticoagulation (RCA) is an optional anticoagulant for plasma adsorption (PA) plus plasma exchange (PE) therapy in patients with acute-on-chronic liver failure (ACLF), but with risk of transient citrate accumulation due to plasma and citrate [ 1 ]. Regardless of the anticoagulants: heparin or citrate, some patients would suffer from longer duration of citrate accumulation (LDCA), defined as the presence of citrate accumulation 2 h after PA plus PE therapy with RCA [ 1 , 2 ]. However, whether citrate accumulation itself would lead to poor prognosis remains uncertain.…”
mentioning
confidence: 99%
“…We conducted a retrospective study based on medical records to assess the association between LDCA and prognosis of hepatitis B virus (HBV)-related ACLF. Methods and some data from this cohort have been published already [ 2 ]. We kept to follow-up these patients for another 90 days after acquiring further ethical approval and registered this study with ChiCTR-OON-17013631.…”
mentioning
confidence: 99%
See 1 more Smart Citation